Zonificación de áreas potencialmente urbanizables en la ciudad de Esquel - Provincia del Chubut con relación a la susceptibilida a inundaciones y remoción en masa - Wright, Eugenia M. (2016)
Esquel is the most important city in the Andean Patagonia in the province of Chubut. It is located in a valley formed by Esquel Creek in between mountains of glacial origin. There is a very strong contrast between East and West climate and environment, with rain, sharp mountains and Andean Patagonia forest to the West, and the transition to the East, with fewer precipitations, less vegetation coverage and gentle relief of plateaus and mountain ranges. Due to natural characteristics, and in addition to no prior plan for land use, lowincome urban expansion takes place in areas prone to floods and landslides. This study analyses the most important variables that are associated to these phenomena. As a result of spatial analysis a susceptibility map was generated to identify risky areas in the city of Esquel and its surroundings.